Circulating Antiangiogenic Factors and Myocardial Dysfunction in Hypertensive Disorders of Pregnancy. Issue 6 (June 2016) - Shahul, Sajid; Medvedofsky, Diego; Wenger, Julia B.; Nizamuddin, Junaid; Brown, Samuel M.; Bajracharya, Surichhya; Salahuddin, Saira; Thadhani, Ravi; Mueller, Ariel; Tung, Avery; Lang, Roberto M.; Arany, Zoltan; et al.
Abstract : Hypertensive disorders of pregnancy (HDP) are associated with subclinical changes in cardiac function. Although the mechanism underlying this finding is unknown, elevated levels of soluble antiangiogenic proteins such as soluble fms-like tyrosine kinase-1 (sFlt1) and soluble endoglin (sEng) are associated with myocardial dysfunction and may play a role. We hypothesized that these antiangiogenic proteins may contribute to the development of cardiac dysfunction in HDP. We prospectively studied 207 pregnant women with HDP and nonhypertensive controls and evaluated whether changes in global longitudinal strain (GLS) observed on echocardiography is specific for HDP and whether these changes correlate with HDP biomarkers, sFlt1 and sEng. A total of 62 (30%) patients were diagnosed with preeclampsia (group A), 105 (51%) did not have an HDP (group B), and 40 (19%) were diagnosed with chronic or gestational hypertension (group C). Blood was drawn and sFlt1 and sEng levels measured using enzyme-linked immunosorbent assay. Comprehensive echocardiograms, including measurement of GLS, were performed on all patients. Overall, GLS was worse in women in group A (preeclampsia) than those in group B or C. Increasing sFlt1 and sEng levels correlated with worsening GLS ( r =0.44 for sFlt1 and r =0.46 for sEng, both P <0.001), which remained significant after multivariable analysis ( r =0.18 and r =0.22, both P ⩽0.01). Increasing levels also correlated with increasing left ventricular mass index, which also remained significant after multivariable analysis ( r =0.20 for sFlt1 and 0.19 for sEng, both P =0.01). Elevated circulating levels of antiangiogenic proteins in HDP correlate with and may contribute to myocardial dysfunction as measured by GLS.